Legionella sainthelensi: a new species of Legionella isolated from water near Mt. St. Helens. - Campbell, J (1984)
Six strains of a new species, Legionella sainthelensi, were isolated from freshwater in areas affected by the volcanic eruptions of Mt. St. Helens in the state of Washington. Strains of L. sainthelensi are culturally and biochemically similar to other legionellae. They grow on buffered charcoal yeast agar but not on media that lack cysteine. They are gram-negative, nonsporeforming, motile rods that are positive in reactions for catalase, oxidase, gelatin liquefaction, and beta-lactamase. They are negative in reactions for urease, hydrolysis of hippurate, reduction of nitrates, fermentation of glucose, and blue-white autofluorescence. Their cell wall fatty acid composition is qualitatively similar to those of other legionellae, with 50 to 62% branched-chain fatty acids. They contain the isobranched-chain 14- and 16-carbon acids and anteisobranched-chain 15- and 17-carbon acids and relatively large amounts of straight-chain 16-carbon acid. All strains of L. sainthelensi contain approximately equal amounts of ubiquinones Q9, Q10, Q11, and Q12, a pattern similar to those of Legionella bozemanii, Legionella dumoffi, and Legionella longbeachae. Serological cross-reactions were observed between L. sainthelensi, both serogroups of L. longbeachae, and Legionella oakridgensis. Three strains of L. sainthelensi were greater than 90% related by DNA hybridization. The type strain of L. sainthelensi, Mt. St. Helens 4, was 36% related to the type strain of L. longbeachae and 3 to 14% related to the other nine described Legionella species.